Fecal Carriage and Epidemiology of Carbapenem-Resistant Enterobacteriaceae Among Hospitalized Patients in a University Hospital - Liu, Qingxia (Infect Drug Resist, 2019)
PURPOSE: To determine the prevalence and epidemiology of fecal carriage of carbapenem-resistant Enterobacteriaceae (CRE), antimicrobial susceptibility, carbapenemase phenotype/genotype, and the colistin-resistance gene mcr-1 in a university hospital in China. METHODS: A comprehensive study of the fecal carriage of CRE in 704 patients was performed. Multilocus sequence typing (MLST) and pulsed-field gel electrophoresis (PFGE) were applied to elucidate the molecular epidemiology of the isolates. RESULTS: In total, 60 CRE were detected in the 704 stool samples (8.5%), including 42 Klebsiella pneumoniae, 7 Escherichia coli, 3 Citrobacter freundii, 3 Klebsiella oxytoca, 3 Enterobacter cloacae, 1 Enterobacter aerogenes, and 1 Raoultella planticola. Fifty-five CRE isolates were positive for the carbapenemase phenotype, of which 39 were Klebsiella pneumoniae carbapenemase (KPC) producers. Thirty KPC-producing K. pneumoniae sequence type (ST) 11 isolates were identified and 28 were grouped into one cluster with a similarity of ≥85%, of predominately intensive care unit (ICU) strains. Three KPC-producing ST1889 strains were isolated from the pediatric ward, all indistinguishable and resistant to tigecycline. All CRE were susceptible to colistin and negative for mcr-1. CONCLUSION: This study revealed a predominant fecal carriage of the KPC-producing K. pneumoniae ST11 clone, with several indistinguishable strain clusters, and the emergence of ST1889 in a Chinese university hospital. This evidence of cross-infection supports the urgent need for the implementation of infection control measures to prevent CRE dissemination.